The duality of disability and aspiration in the children’s stories of Nadia Al-Najjar - Alhashemi, Badeeah (Al-Adab Journal, 2024)
The story is one of the most beloved literary arts among children, and one of the most successful in achieving the desired educational goals, away from direct directions, orders, and prohibitions. Among the most important of these goals: social, psychological, moral and humanitarian. Dealing with the subject of (people with special needs) is considered one of the important social and humanitarian issues that children’s writers should address in their stories. And then they must be very careful in dealing with the ideas they put forward; Due to the specificity and sensitivity of the issue. Writers must be sufficiently aware of the appropriate method that is compatible with the awareness and mental awareness of the target stage. They must also understand the scientific, psychological and social foundations that will help him present the subject to their young readers. And because it is not possible to separate the content and the form in the literary text, the narrator must employ the elements of artistic construction in the child’s story in a manner consistent with its subject matter. to come explaining to him, consistent with him. Starting from the title of the story, all the way to its conclusion, without ignoring the visual discourse represented in images, drawings and colors, which is another language adjacent to the written language of the story. The Emirati writer Nadia Al-Najjar is one of the most prominent writers who presented this topic in a number of her stories. It has dealt with various cases of disability in an interesting and artistic manner, taking into account the educational, psychological and social standards that children’s literature targets. This research deals with four of them with study and analysis on the objective and artistic levels, namely: “I am different”, “Voices of the World”, “My Wonderful Walk with Uncle Salem”, and “Yellow Sea… Green Sand”, employing the descriptive and analytical approach.